Safety and Labor Health, Corporate Social Responsibility with Return of Economic Benefits - Jesus Ernesto Rocha-Ibarra; Yashiro. Danahi Cisneros-Reyes (European Scientific Journal, ESJ, 2018)
This article is a quantitative and qualitative case study of the Self- Management Program Occupational Safety and Health (P.A.S.S.T.) implemented in twenty-five Mexican companies. The analysis is based on the theories of business ethics, corporate governance and the concept of publicprivate partnerships to explain the achieved link by the Ministry of Labor and Social Prevision (S.T.P.S) and the Private Initiative to improve the safety conditions and health within the companies. After reviewing the results of the data obtained by the companies, it was found that there are financial benefits and quality in processes, derived from the good corporate governance.